Highly stable aqueous phase black phosphorus quantum dots with enhanced fluorescence property. (20th July 2022) - Ma, Yingli; Xu, Xiaoguang; Zhang, Xiaoshuang; Rong, Mayifei; Lu, Liying; Li, Yan; Dai, Wenhao; Du, Hongwu; Jiang, Yong
Highlights: BPQDs with good crystallinity were designed and synthesized by a facile approach in water. Aqueous BPQDs exhibit excellent PL performance with an absolute QY of 11.5% and high stability more than six months because of the modification and passivation of NH2 -PEG-NH2 . BPQDs are promising candidate as fluorescence probes for Fe 3+ and bioimaging agents. Abstract: Black phosphorus quantum dots (BPQDs) are a kind of outstanding optical material due to the tunable band structure. However, their fluorescence property and stability are obviously weakened in the aqueous phase, which extremely restricts the development of BPQDs. Here, we propose a new method to prepare stable BPQDs in an aqueous solution directly with high absolute fluorescence quantum yield. Aqueous phase BPQDs are synthesized by liquid exfoliation and hydrothermal with NH2 -polyethylene glycol (PEG)-NH2 as the modification agent to protect the BPQDs, which have high stability more than six months. In addition, NH2 -PEG-NH2 is also a surface passivation agent to enhance the emission of BPQDs by forming P–N bonds, which is confirmed by an absolute fluorescent quantum yield of 11.5%. Moreover, BPQDs show excellent resistance to a strong acid environment and high ionic strengths except for Fe 3+ . Therefore, the BPQDs are a kind of highly selective and linear response fluorescence probe for Fe 3+ . Considering the good biocompatibility of BPQDs, they are employed as cell fluorescent label probes and show excellent fluorescence imaging contrast. Based on the unique structural stability and fluorescence performance in the aqueous phase, BPQDs are potential candidates for Fe 3+ detection and optical bio-imaging.